Mitraclip for high risk patients with barlow mitral valve disease. (25th November 2020) - Gavazzoni, M; Taramasso, M; Voci, D; Pozzoli, A; Miura, M; Tagliari, A.P; Zuber, M; Maisano, F
Abstract: Background: No data have been published to now about the outcomes of MitraClip in inoperable patients with Barlow's Mitral Valve Disease. Despite the technical advantages of the new generation of MitraClips, the length and the thickness of the mitral leaflets and presence of flails with complete eversion and pseudo-cleft are challenging MitraClip procedure. Purpose: To analyse the results of MitraClip in inoperable patients with Barlow's disease of Mitral valve. Methods: We retrospectively collected the cases of MR in Barlow's disease treated with MitraClip in our institution from 2012 to 2018. The case were included in the analysis in presence of the following characteristics: bileaflet billowing or prolapse [or both], excessive leaflet tissue, and annular dilatation with or without calcification. Results: We included in this analysis 59 patients (mean age 78±8 years, STS mortality score 4±2.9%). Echo data at baseline showed normal left ventricle ejection fraction and diastolic volume and increased left atrial volume index. Half of the included patients had a chordal rupture (n=27, 47%) and in 14 patients (23%) calcification of annulus and/or leaflet was diagnosed. The mean procedural time was 92±41min with a technical success (M-VARC) of 100% and more than 80% of patients requiring more than 1 clip. At 30 days follow-up the device success and the procedural success were respectively 59% and 56%. The mean diastolic mitral valve gradient was 3.1±1.5mmHg. At 30 days follow-up, 91% of the patients were NYHA class II stable patients; no death and no hospitalization occurred. During a median follow-up time of 412 days (IQR: 209–992 days) death for any cause occurred in 23% of the patients (n=14) and 16% of the patients (n=10) died because of a cardiovascular cause; 10 patients were re-hospitalized for heart failure and 5% of the patients (n=3) underwent an open-heart surgery at follow-up time. At univariate cox regression analysis the 1-Y composite end-point (death for any cause, HF re-hospitalization, MV surgery) was predicted by LV dimensions and 30 days procedural success. Conclusions: To our knowledge, this is the first analysis of outcomes of Barlow's disease treated with MitraClip. Despite a high incidence of MR recurrence, we observed a good clinical response in term of NYHA class and mortality rate. Left ventricle size and 30-day procedural success predict outcomes. Funding Acknowledgement: Type of funding source: None